Tourism and justice: Rethinking the role of governments. (November 2020) - Rastegar, Raymond
Highlights: Provides unique context to explore the role of government as a strong stakeholder Social justice can be misused to exclude communities from decision-making process. Perspectives of either ecological justice or social justice can create conflicts. Provides opportunities to design tourism that builds on the principles of justice The time has come to move forward and give communities a voice.